Akuntansi Forensik Untuk Bedah Kasus Korupsi - Gita Claudia (JEMAP, 2018)
This study aims to see corruption case of driving license simulator procurement project from the forensic accounting side. The number of corruption cases in Indonesia has prompted the government to order all central and regional authorities to carry out any measures to combat corruption. The role of forensic accountants is needed in order to dismantle the number of fraud that comes from corruption. Forensic accounting provides an accounting analysis that can be used for debates in court which are the basis for discussion and resolution in court.A forensic accountant is someone who understands forensic accounting. Forensic accountants have specialized expertise in accounting, auditing, finance, quantitative methods, specific areas of law, research, and investigative skills in gathering evidences, analyzing evidence, evaluating evidence, interpreting and communicating the results of the findings. This research explains the corruption case of driving license simulator project procurement of document evidence, physical evidence, testimonial evidence, and personal observation. From the findings of evidence by the forensic accountant, that can help solve the case of corruption driving license simulator procurement project.